FORMULATION AND EVALUATION OF EAU DE PARFUME (EDP) FLORAL AROMA CHARACTERISTICS - Putri, Tikarahayu; Handayani, Kiki Yuli; Reza, Muhammad (Indonesian Journal of Cosmetics, 2023)
Currently, perfumes have emerged as highly sought-after cosmetic products in the Indonesian consumer market, aligning with the demands of daily life for enhanced self-assurance. Various types of perfume are categorized based on the ratio of fragrant oil content to solvent. Presently, the prevailing perfumes available in the market predominantly belong to the category with low concentrations of fragrant oils. The principal objective of this research is to formulate a product recipe for Eau de Perfume (EDP) with sweet and floral characteristics. The methodology employed in this study is experimental and consists of two phases: perfume formulation, evaluation, and final product development. The evaluation conducted in this research encompasses organoleptic and physical assessment, aroma longevity testing, spot testing, hedonic evaluation, and sensory testing. Based on the data collected from the research results, it can be concluded that the perfumes with longer aroma longevity are formulas F1 and F2. The average area of EDP spray dispersion is 74,48 mm. The most preferred hedonic test result was obtained from formula F2. Organoleptic test data for all formulas showed a clear and particle-free, the colorless solution observed after one month of storage. The solution’s viscosity increased during the fourth week due to the partial evaporation of the solvent. Sensory analysis results revealed that the aroma of all three formulas was characterized as sweet with floral undertones.